Pemahaman Guru Taman Kanak-kanak (TK) Terhadap Aktivitas Jasmani Bagi Anak TK Se-Kecamatan Padang Jaya: Kindergarten (TK) Teachers Understanding of Physical Activities for Kindergarten Students in the District of Padang Jaya - Pety Nurbaeti; Yahya Eko Nopiyanto; Septian Raibowo (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Abstract This study aim to determine the understanding of kindergarten teachers (TK) on physical activity for kindergarten students in Padang Jaya District. This study used a qualitative method. The subjects in this study were 8 kindergarten teachers in Padang Jaya District. The instruments and data collection techniques used in this study were observation, interviews, and questionnaires. The results of observational research get a score of 75% (medium), 25% (high), while the results of the questionnaire get a percentage value with an average of 56.11%. Based on the results of the study, it can be seen that the level of understanding of kindergarten (TK) teachers on physical activity for kindergarten children in the Padang Jaya District is categorized as moderate because teachers already have an understanding of physical activity, but there are still teachers in the implementation of teaching and learning that is not in accordance with predetermined learning program. The importance of understanding kindergarten teachers on physical activity to support children can move actively through their gross motor skills. Keywords: Physical Activity, Teacher, Understanding, Students, Kindergarten.AbstractThis study aim to determine the understanding of kindergarten teachers (TK) on physical activity for kindergarten students in Padang Jaya District. This study used a qualitative method. The subjects in this study were 8 kindergarten teachers in Padang Jaya District. The instruments and data collection techniques used in this study were observation, interviews, and questionnaires. The results of observational research get a score of 75% (medium), 25% (high), while the results of the questionnaire get a percentage value with an average of 56.11%. Based on the results of the study, it can be seen that the level of understanding of kindergarten (TK) teachers on physical activity for kindergarten children in the Padang Jaya District is categorized as moderate because teachers already have an understanding of physical activity, but there are still teachers in the implementation of teaching and learning that is not in accordance with predetermined learning program. The importance of understanding kindergarten teachers on physical activity to support children can move actively through their gross motor skills.Keywords: Physical Activity, Teacher, Understanding, Students, Kindergarten.